ANALISA PENGARUH SUHU AWAL PELAT PANAS PADA PROSES QUENCHING CELAH SEMPIT REKTANGULAR - Kusuma, Muhammad Hadi; Juarsa, Mulya; Antariksawan, Anhar Riza; Putra, Nandy (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2013)
The understanding about thermal management in the event of a severe accident such as the melting nuclear reactor fuel and reactor core, became a priority to maintain the integrity of reactor pressure vessel. Thus the debris will not out from the reactor pressure vessel and resulting impact of more substantial to the environment. One way to maintain the integrity of the reactor pressure vessel was cooling of the excess heat generated due to the accident. Toget understanding of this aspect, the research focused on the effect of the initial temperature of the hot plate in the rectangular narrow gap quenching process. The initial temperature effect on quenching process is related to cooling process (thermal management) when the occurrence of a nuclear accident due to loss of coolant accident or severe accident. In order to address the problem, it is crucial to conduct research to get a better understanding of thermal management regarding to nuclear cooling accident. The research focused on determining the rewetting temperature of hot plate cooling on 220 0C, 400 0C, and 600 0C with 0.2 liters/sec cooling water flowrate. Experiments were carried out by injecting 85 0C cooling water temperature into the narrow gap at flowrates of 0.2 liters/sec. Data of transient temperature measurements were recorded using a data acquisition system in order to know the rewetting temperature during the quenching process. This study aims to understand the effect of hot plate intial temperature on rewetting during rectangular narrow gap quenching process. The results obtained show that the rewetting point on cooling the hot plate 220 0C, 400 0C and 600 0C occurs at varying rewetting temperatures. At 220 0C hot plate initial temperature, the rewetting temperature occurs on 220 0C. At 400 0C hot plate initial temperature, the rewetting temperature occurs on 379.51 0C. At 600 0C hot plate initial temperature, the rewetting temperature occurs on 426.63 0C. Significant differences of hot plate initial temperature leads to changes in physical properties of material, different boiling regimes occurs when fluid passing through a narrow gap, changes on specific heat of material, changes on thermal conductivity of material, and the differences of wall superheated temperature. Rewetting temperature will increase due to increasing on hot plate initial temperature.